Optimalisasi Potensi Wisata Desa Pabean Dengan Pengembangan Website Desa - Hendra Maulana; Sheidy Yudhiasta; Latif Ahmad Fauzan; Ardhelia Damayanti Wirawan; Adham Roy Bhafiel (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Pabean Village is one of the villages in Dringu District, Probolinggo Regency, which has tourism potential that needs to be developed, namely Tugu Beach. In the development process, there are several problems faced, one of which is the lack of uploads related to information on the condition of Tugu Beach. This lack of information resulted in a decrease in visitors who came. So that the community service team of the Veteran National Development University of East Java provides a solution by making a village website to support the digitization of village potential development. This research was conducted to observe how the community is impacted by the digitalization step in sharing information. The research was conducted using interview and observation methods in the environment around Pabean Village and Tugu Beach. The results of interviews and observations will be used as information material to be uploaded on the website. The result of this activity is that the website is symbolically given to the village. The village received it well and hopes that with this step, the potential of Pabean Village will increase.